PLANT EXTRACT ADDITION FOR IMPROVED METHANE POTENTIAL OF TUBER PEEL - Danmallam, Aisha; Agbaji, E. B.; Nwokem, N. C.; Sani, U.; Nwokem, C. O. (FUDMA JOURNAL OF SCIENCES, 2020)
The percentage yield of methane in biogas ranges from 40 – 70 %, which is relatively low when compared to natural gas whose methane composition is about 90 %. Improving the methane yield will increase the efficiency of the biogas to some extent. As a result, the use of plant additives is employed to improve the methane gas yield of the biogas produced. Methane gas production from starch-rich tuber peel was investigated at laboratory scale using a batch anaerobic digester of two litres working volume at mesophilic temperature. The digesters were fed with slurry of dry tuber peel and operated for sixty (60) days. Initially, 42 % methane production was recorded. The effect of the volume (100, 300 and 500 cm3) of aqueous extracts of soya, neem and water hyacinth on methane gas yield was also studied. An increase in methane production over the control was recorded in all the digesters. Significantly higher levels of methane gas production were observed in the digesters to which 500 cm3 of aqueous extract was added with the neem extracts recording the highest.